An artificial-enzyme-equipped immunoregulator blocks platelet-mediated breast cancer hematogenous metastasis - Hu, Ben; Lin, Huimin; Quan, Xiaolong; Sun, Fushan; Zhang, Fengling; Zhang, Fang; Wang, Yu; Chang, Yunhua; Wang, Jigang; Duan, Xiaohui; Yu, Meng (Biomaterials, 2025)
Platelet activation and adhesion on the surface of circulating tumor cells (CTCs) assist them in surviving within the vasculature and acquiring enhanced migratory potential. Simultaneously, protected by surrounding/covering "micro-thrombi," CTCs evade immune surveillance in circulation, thereby promoting hematogenous tumor metastasis. Based on this, we designed a self-assembling nanoenzyme drug GSNO@B (NO donor-modified GOx self-assembled with the hydrophobic drug BMS-202) against platelet-mediated tumor metastasis. This strategy involves the depletion of glucose by GOx, which inhibits platelets activity and reduces forming the micro-aggregation. Concurrently, the nanoenzyme in situ releases NO further diminishes the protective adhesion and micro-aggregation of platelet on the tumor cells surface, thereby exposing them in shear forces and immune recognition in the circulatory system. Concurrently, the disintegration of the nanoenzyme GSNO@B releases the immune checkpoint inhibitor BMS-202, further facilitating the immune clearance of CTCs. Therefore, through a three-step strategy, GSNO@B effectively suppresses primary tumors growth and metastatic tumors formation by blocking the platelet-mediated hematogenous tumor metastasis pathway.